Multi-frequency polarimetric SAR signatures of lead sea ice and oil spills - Johansson, Malin; Brekke, Camilla; Spreen, Gunnar (2017 IEEE International Geoscience and Remote Sensing Symposium (IGARSS), 2017)
Synthetic aperture radar is used to identify and monitor oil spills. Separation from oil spill look-alikes is an important part of a fully automatic oil spill detection scheme. Here we investigate the polarimetric signatures for oil spills and newly formed sea ice (a well-known look-alike) in fully polarimetric Radarsat-2 satellite scenes. Using the fully polarimetric scenes we calculate four different parameters, co-polarization ratio, polarization difference, scattering entropy, and mean alpha angle. Three pairs of satellite scenes with comparable incidence angles are used. We observe that a combination of the co-polarization ratio and the polarization difference enables us to delineate the spills from their surrounding and also to discriminate the oil spills from the newly formed sea ice. The scattering entropy and the alpha values provide additional information about the scattering mechanisms of sea ice and oil spills.